EFEKTIVITAS PENGGUNAAN ALAT PERAGA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA MATA PELAJARAN IPAS MATERI BAGIAN-BAGIAN TUMBUHAN KELAS IV SDN BENDUNGAN I KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG TAHUN PELAJARAN 2024/2025 - Ikhsan, MT Hartono; Citra Irgaeni; Ria Kurniasari; Encep Iman Hadi Sunarya (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effectiveness of using visual aids in improving the creative thinking skills of fourth-grade students in the subject of Science and Social Studies (IPAS), particularly on the topic of plant parts. The background of this research is the low level of students’ creative thinking abilities, which is attributed to the dominance of conventional teaching methods that do not incorporate visual aids. This study employed a quantitative approach with a pre-experimental design using the One-Group Pretest-Posttest model. The research subjects were 25 fourth-grade students at SD Negeri Bendungan 1. The instrument used was a test based on creative thinking indicators: fluency, flexibility, originality, and elaboration. The analysis results showed that the data were normally distributed, and the paired sample t-test yielded a significance value of 0.000 < 0.05. This indicates a significant difference between the pretest and posttest scores. Therefore, it can be concluded that the use of visual aids is effective in enhancing students’ creative thinking skills in IPAS learning